Low sodium, big flavor : 115 recipes for pantry staples and daily meals - Ferroni, Lara (Sasquatch Books, 2021)
"A flavorful cookbook with approximately 100 recipes for anyone who is on a low sodium diet who wants to enjoy food again!"--